The EpSSG NRSTS 2005 treatment protocol for desmoid-type fibromatosis in children: an international prospective case series. (December 2017) - Orbach, Daniel; Brennan, Bernadette; Bisogno, Gianni; Van Noesel, Max; Minard-Colin, Véronique; Daragjati, Julia; Casanova, Michela; Corradini, Nadege; Zanetti, Ilaria; De Salvo, Gian Luca; Defachelles, Anne Sophie; Kelsey, Anna; et al.
Summary: Background: In 2005, the European Pediatric Soft Tissue Sarcoma Study Group (EpSSG) proposed a conservative treatment algorithm—consisting of an initial wait-and-see strategy, non-mutilating surgery, and minimal-morbidity chemotherapy (in the case of tumour progression)—for paediatric patients with desmoid-type fibromatosis. We aimed to investigate the outcomes of this algorithm. Methods: In this case series, patients (<25 years) with desmoid-type fibromatosis from 57 centres in eight countries were prospectively registered through a web-based system. Diagnosis was based on histological analysis of the tumour specimen after biopsy or surgery, and we classified patients by tumour site, clinical stage (TNM system), and post-surgical stage (Intergroup Rhabdomyosarcoma Study system). Progression-free survival was defined as the time from diagnosis until disease progression (clinical or radiological progressive disease, relapse, or death from any cause). Findings: From Oct 1, 2005, to July 31, 2016, 173 patients (median age 11·4 years [IQR 4·0–14·1], 88 [51%] male patients) were registered. After excluding patients with missing data, 54 (35%) patients had no immediate therapy (wait-and-see strategy), 47 (31%) had immediate surgery, and 53 (34%) had immediate chemotherapy after diagnosis. 5-year progression-free survival was 36·5% (95% CI 27·8–45·2) overall, 26·7% (14·2–41·0) in the wait-and-see group, 41·2% (25·8–55·9) in the surgery group, and 42·8% (27·2–57·6) in the chemotherapy group (overall log-rank p=0·17; wait-and-see vs surgery p=0·12; wait-and-see vs chemotherapy p=0·13). In multivariable analysis, large tumour size (>5 cm) was associated with worse progression-free survival (hazard ratio 2·25, 95% CI 1·34–3·76; p=0·0021). Apart from one patient in the chemotherapy group who died from a secondary tumour (head and neck anaplastic embryonal rhabdomyosarcoma), all patients were alive at the time of analysis. 13 (8%) patients had biopsy only (no further treatment), 65 (42%) had chemotherapy only, 31 (20%) had surgery only, 36 (23%) had both chemotherapy and surgery, and nine (6%) had radiotherapy in addition to other therapies. Interpretation: In paediatric patients with desmoid-type fibromatosis, the EpSSG conservative strategy did not compromise outcomes and could be adopted to reduce treatment burden. Funding: S Wisnia and la Città della Speranza Foundation.